DURATION OF GADGET USE AND FINE MOTOR DEVELOPMENT IN FOUR YEARS CHILDREN AT PUTRA BANGSA PRE-SCHOOL - Anik Nuridayanti; Citrawatik Dwi Skripsia; Slamet Jayadi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Gadget is a modern device which used as a means of communication and many more functions either for children or adults, and can make addicted. It also has influences to development of children’s soft motoric nerves. The objective of this research is to know the relation between gadget usage duration and soft motoric nerves development of 4 years old children in PAUD Putra Bangsa Wajak Lor, Tulungagung Regency.The design of this research was correlational analytics with cross-sectional approach. The population was all of PAUD Putra Bangsa Wajak Lor and and 24 respondents were taken as samples by purposive sampling technique. The independent variable was the duration of gadget usage, and obtained from questionnaires, and the dependent variable was the development of 4 years old children’s soft motoric nerves which obtained from observation. The data analyzed with Spearman Rank Test. The research result were almost all of the respondents or (62.5%) used gadgets the most frequently (66.7%) of the respondents developments of soft motoric nerves were suspected. There was a negative and strong relation between gadget usage duration and the development of 4 years old children’s soft motoric nerves (Spearman Rank, p value 0.000 < 0.05, Correlation Coefficient : -0.668). The conclusion was the higher the duration of the use of gadgets then the development of 4 years old children’s soft motoric nerves in the suspect category, so that need role existence parents for the limit duration usage gadgets on child.